2014
DOI: 10.5455/cap.20131229101314
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behavior in Elderly

Abstract: ÖzetTüm dünyada olduğu gibi Türkiye'de de yaşlı nüfusun oranı hızla artmaktadır. Buna paralel olarak, ileri yaşta görülen psikiyatrik hastalıklar ve intihar önem kazanmaktadır. Yaşlı intiharları çok ciddi bir halk sağlığı sorundur. Yaşlılık dönemi intihar davranışları ölme isteğinden tamamlanmış intiharlara kadar geniş bir çerçevede izlenmektedir. Yaşlı nüfusta intihar için risk faktörleri erkek cinsiyet, düşük sosyoekonomik düzey, sosyal izolasyon, umutsuzluk ve bağımlılık gibi kişilik özelliklerinin olması, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
1
7
1
1
Order By: Relevance
“…In addition, the suicide rates in men in the geriatric age group were reported to be higher than the general age group. (12) In the general population, unlike our study, suicide attempts were higher in the females. (13) The suicide rates in the geriatric age group are reported to be highest in the age group of 75 years and over.…”
Section: Discussioncontrasting
confidence: 66%
“…In addition, the suicide rates in men in the geriatric age group were reported to be higher than the general age group. (12) In the general population, unlike our study, suicide attempts were higher in the females. (13) The suicide rates in the geriatric age group are reported to be highest in the age group of 75 years and over.…”
Section: Discussioncontrasting
confidence: 66%
“…The basic reason for this is that there is a tendency to shield victims of suicide because it is an act that is not endorsed from a social and religious aspect (Sayıl, 1994;Uçan, 2005;Aslan, Hocaoğlu, 2014). The data pertaining to the reasons for suicide is the most problematic area in terms of suicide related data.…”
Section: Research Materials and Methodsmentioning
confidence: 99%
“…Older adults face many problems, such as retirement, changes in social roles, intergenerational conflict, chronic illness, loss of skills and influence, loss of relatives and friends, economic losses, dependence on other people, loneliness, and hopelessness. The relationship between these problems and suicide in older adults is still a matter of concern …”
Section: Introductionmentioning
confidence: 99%
“…Suicide is a conscious, violent, self‐mutilating behavior, in addition it is still a significant public health concern and a leading cause of death among older adults. Suicide can be a reaction to stressful life conditions, as well as a result of serious psychological disorders . Studies have shown that suicide rates increase with age, and the greatest increase is in older adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation